Cyclic behavior and fatigue resistance of AISI H11 and AISI H13 tool steels. (March 2021) - Riccardo, Gerosa; Rivolta, Barbara; Gorla, Carlo; Concli, Franco
Highlights: During the cyclic tests, softening was observed for both the investigated materials, even if the AISI H13 strength reduction was slightly more than AISI H11 one. The low cycle fatigue properties of AISI H11 and AISI H13 steels are similar for temperature up to 350 °C. At 550 °C, there is a remarkable influence of the creep and of the oxidation on the cyclic behavior of both the steels with a clear reduction of the fatigue life. For AISI H13 steel, creep tests were carried out to separate the creep contribution from the fatigue and the oxidation ones. The data analysis revealed that fatigue and oxidation are the main contributions at 550 °C. Abstract: The present experimental work investigates the isothermal low cycle fatigue resistance of two well-known tool steels, AISI H11 and AISI H13, at four different temperatures: ambient, 200 °C, 350 °C and 550 °C. The characterization of the steels included tensile and creep tests too. The tensile, the creep and the cyclic properties are in fact often employed to assess the thermal fatigue of a material. The fatigue tests up to 350 °C resulted in similar strain-cycles to fracture curves, whereas the ones performed at 550 °C were significantly different. A deep analysis was hence carried out to distinguish the contribution of the fatigue, of the creep and of the oxidation. It was found that at 550 °C fatigue and oxidation are the main driving mechanisms. Finally, the fracture surfaces were observed both by stereo and scanning electron microscopes. Multiple crack nucleation was observed, especially for the tests at high temperature.